The Implementation of Integrated Project-Based Learning Science Technology Engineering Mathematics on Creative Thinking Skills and Student Cognitive Learning Outcomes in Dynamic Fluid - Herta Astri Yudika Sinurat; Syaiful Syaiful; Damris Muhammad (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
This study aims to determine the effect of implementing STEM-integrated PJBL on students' creative thinking skills and cognitive learning outcomes. This research is quasi-experimental with a two-group pretest-posttest design. The research population is all grade 11th IPA SMAN 3 Bungo students, and the sample was determined by random sampling. Three projects conducted by the students were water pump free energy, fountain free energy, and air bubble generator. Two instruments of creative thinking test in essay form and multiple-choice for learning outcome test were used. The averages of pretest results of creative thinking and learning outcomes were 27.97 and 30.00 for the experiment class and 30.16 and 30.31 for the control, respectively. This shows that initial student ability in both the creative thinking skill and learning outcome of both types are level. STEM integrated PJBL was then used in the experiment class, and a conventional learning strategy was used for the control class. The average posttest results indicate that the student creative thinking skill of the STEM integrated PJBL class (82.81) is significantly higher than that of the control (36.72). Contrast with the posttest learning outcome showed no difference. These results show that the students actively engaged with the projects in the STEM integrated PJBL class improved their creative thinking skills significantly compared to the control class. This research's main finding is that implementing the STEM-integrated PJBL effectively enhances students' creative thinking skills. Manova analysis shows the students of the experiment class scored 76% in high and 63% in medium categories for both the creative thinking skills and learning outcome, respectively.